Evidence of lophophore diversity in early Cambrian brachiopoda. - Zhang, Xi-Guang (2003)
The lophophore, an essential organ of the Brachiopoda, has been used widely in evolutionary and advanced phylogenetic studies, but is hitherto unknown in the fossil record. Here, the extraordinarily well-preserved lophophores of two inarticulated brachiopods Lingulella chengjiangensis and Heliomedusa orienta, from the Lower Cambrian Chengjiang fauna (Yunnan, China) are described. These primitive lophophores, respectively, trocholophous and schizolophous, have some key characters that may be plesiomorphies inherited by their recent descendants. This discovery provides direct evidence regarding the taxonomy, ecosystems and early evolution of inarticulated brachiopods.